Gums and stabilisers for the food industry 15 - Williams, Peter A.; Phillips, Glyn O. (Special publication (Royal Society of Chemistry (Great Britain)), 2010)
The book describes the new advances in the science and technology of hydrocolloids which are used in food and related systems. The focus is on the technofunctionality and the biofunctionality of hydrocolloids, giving an appropriate emphasis to the manipulative skills of the food scientist and recognising the special part hydrocolloids can play in supporting human health. Gums and Stabilisers for the Food Industry 15 captures the latest research findings of leading scientists which were presented at the Gums and Stabilisers for the Food Industry Conference at the Glyndwr University, Wrexham, UK.